Antiobesity, Antihyperglycemic, and Antidepressive Potentiality of Rice Fermented Food Through Modulation of Intestinal Microbiota - Hor, Papan Kumar; Pal, Shilpee; Mondal, Joy; Halder, Suman Kumar; Ghosh, Kuntal; Santra, Sourav; Ray, Mousumi; Goswami, Debabrata; Chakrabarti, Sudipta; Singh, Somnath; Dwivedi, Sanjai K.; Takó, Miklós; et al. (Frontiers in Microbiology, 2022)
The present study has been aimed at evaluating the antiobesity, antihyperglycemic, and antidepressive potentials of Asparagus racemosus starter-based rice fermented foods. High-throughput NGS technology has revealed a number of bacterial genera in the prepared fermented rice, such as Lactobacillus (29.44%), Brevundimonas (16.21%), Stenotrophomonas (6.18%), Pseudomonas (3.11%), Bacillus (2.88%), and others (<2%). Eight-week administration of rice fermented food has increased food intake, whole-body weight, organ weight, different fat masses, serum lipid profiles, and histology of liver and adipose tissues in HFD-induced obese mice. In addition, upregulation of fatty acid oxidation and downregulation of adipocytogenesis- and lypogenesis-related genes along with the expression of their regulatory nuclear factors such as PPARα, PPARγ, PPARδ, and SREBP-1c have also been noted. Moreover, fermented food decreases fasting blood glucose level and improves glucose and insulin tolerance as well as the expression of GLUT4 receptor. Antiobesity and antihyperglycemic effects are also supported by the changes in insulin, leptin, and adiponectin hormone levels. The real-time polymerase chain reaction (RT-PCR) and denaturing gradient gel electrophoresis (DGGE) analyses have clearly demonstrated the intense colonization of Bacteroides, Lactobacillus, and Bifidobacterium, as well as the suppressed growth rate of γ- and δ-Proteobacteria and Firmicutes in the gut after fermented food intake. In the intestine, the latter group of microorganisms possibly modulate short-chain fatty acid (SCFA) levels such as acetate, butyrate, and propionate more than twofold. The impairment of memory-learning and anxiety-like obesity-associated cognitive phenotypes is mitigated significantly (p < 0.01) by fermented food as well. Thus, the formulated fermented food could be used as a natural therapeutic to alleviate obesity and its associated psychological and pathophysiological ailments.